A Discourse Analysis of Radio Call ins In Runyankore-Rukiga. - Niwamanya, Diana (Kabale University, 2025)
This study conducted a discourse analysis of radio call-ins in Runyakore Rukiga transcripts to investigate the use of discourse markers to analyze conversation structures and compare them in communication. This study was designed to evaluate the discourse of radio call-ins in Runyakole Rukiga across social, political, and religious contexts. Recordings of a show going on were made and then transcribed into written information The researcher recorded five callers during the chosen shows namely The Wind Down Show, Tumuhimbise, Ekizungilizi, and The Day Blender. The recordings of the five callers in these shows were then translated from the local language which is Runyankore Rukiga to English. The translation was then presented to a bilingual speaker of Runyankore–Rukiga and English for verification and discourse analysis of the data. Analysis of the transcribed data revealed a broad stream of discourse markers. The findings revealed how the conversation structures differ in the different structures. By analyzing the structure of these conversations, we identify patterns and functions of discourse markers, such as turn-taking, topic shifts, and signaling agreement or disagreement. The findings reveal that certain markers are context-specific, with distinct uses in social, political, and religious discussions. For instance, in social contexts, markers like ‘I think’ and ‘you know’ are common, while political discussions often feature markers like ‘in my opinion’ and ‘I believe.’ Religious call-ins show a higher frequency of markers that express reverence or deference, such as ‘Lord’ or ‘bless you.’ This research contributes to our understanding of how discourse markers shape interactions in different social domains and highlights the importance of context in discourse analysis.